Persuasive Strategies in Green Sustainability Advertisements: A Pragmatic Study (المجلة الدولية للبحوث العلمية, 2025)
The way language is styled and structured is a way to manipulate, thus, a way to capturing hearts. This study investigates the effect of language and in green sustainability protests and advertisements. This is a pragmatic study that examines the language used in green sustainability media and protest advertisements by the use of persuasive language. In linguistics, persuasive language either conveys its message through the use of powerless style or through powerful style. This is known as persuasion, in linguistic studies. Persuasion, in linguistics, is the power of words. Persuasion is using words to communicate ideas in a certain way and makes us think or do something in a particular manner. Green sustainability advertisements are, indeed, linguistic persuasion at hand, using the linguistics of persuasion to manipulate language. The language used by green sustainability advocates is thought of very intensively to influence the audience. They know that language is a powerful tool. It is our means to communicate in getting our message across and negatively or positively influencing others around us.